2017
DOI: 10.1016/j.precamres.2017.03.006
|View full text |Cite
|
Sign up to set email alerts
|

The syn-orogenic sedimentary record of the Grenville Orogeny in southwest Laurentia

Abstract: Late Mesoproterozoic sedimentary sequences in southwest Laurentia range in age from 1340 to 1035 Ma and record regionally extensive intracratonic sedimentation before and during the Grenville Orogeny in southern Laurentia. This paper examines the specific links between intracratonic sedimentation and orogenesis and develops a new tectonic model for basin formation throughout southwest Laurentia during the Late Mesoproterozoic. New detrital zircon, muscovite, and biotite ages refine the provenance, depositional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 143 publications
1
23
0
Order By: Relevance
“…Most of these sequences were deposited at considerable distance from the Grenville Orogen, implying their detritus was transported across Laurentia by continental-scale river systems (Rainbird et al, 1992(Rainbird et al, , 1997(Rainbird et al, , 2012. Similarly, remnants of more distal deposits, sourced from the Grenville Orogen occur in the southern United States (e.g., Mulder et al, 2017). These distal sequences were not deposited in foreland basins sensu stricto, that is basins in which accommodation space is primarily created by the load of the adjacent mountain belt (e.g., Beaumont, 1981;Jordan, 1995).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of these sequences were deposited at considerable distance from the Grenville Orogen, implying their detritus was transported across Laurentia by continental-scale river systems (Rainbird et al, 1992(Rainbird et al, , 1997(Rainbird et al, , 2012. Similarly, remnants of more distal deposits, sourced from the Grenville Orogen occur in the southern United States (e.g., Mulder et al, 2017). These distal sequences were not deposited in foreland basins sensu stricto, that is basins in which accommodation space is primarily created by the load of the adjacent mountain belt (e.g., Beaumont, 1981;Jordan, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…The basin fill, deposited between 1130-1035 Ma, consists of fluviatile siltstone and conglomerate and is deformed into late Grenvillian, km-scale recumbent folds (Soegaard and Callahan, 1994;Grimes and Mosher, 2003;Mulder et al, 2017). Hoffman, 1988;Buchan et al, 2000;Rivers et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Comparison of detrital zircon ages of metasedimentary rocks with similar depositional age in the Chinese CTB and Yili Block (this study; Huang et al, ), North Australia, West Australia, and South Australia (Smiths et al, , and references therein), West Laurentia (Hadlari et al, ; Howard et al, ; Lane et al, ; Lane & Geherls, ; Leslie, ; Mulder et al, , ; Spencer et al, ; Stewart et al, ; Tomas et al, ), and Fennoscandia (Bingen et al, ; Pulsipher & Dehler, ).…”
Section: Discussionmentioning
confidence: 64%
“…It is thus suggested that the Cathaysia Block was not adjacent to the CTB. Among the main blocks worldwide, the Western Laurentia displays an age peak at 1.4–1.5 Ga, close to that of the CTB (Figures a and e; Hadlari et al, ; Howard et al, ; Lane & Geherls, ; Lane et al, ; Leslie, ; Mulder et al, , ; Spencer et al, ; Stewart et al, ; Tomas et al, ). However, ca.…”
Section: Discussionmentioning
confidence: 91%
“…We find that the Jacobsville's zircon age distribution differs from that observed elsewhere for sedimentary rocks in North America's interior derived from the Grenville orogeny, such as Middle Run and equivalent sandstones in Ohio and Kentucky (Baranoski, Dean, Wicks, & Brown, 2009; Santos et al., 2002), in the Amundsen and Mackenzie basins of northwest Canada (Rainbird et al., 2017), and in the Hazel Formation of Texas (Spencer, Prave, Cawood, & Roberts, 2014). The Jacobsville has a relatively small percentage of zircons from the Ottawa (1,090–1,030 Ma) phase, but a larger percentage of Shawinigan (1,200–1,140 Ma), like rocks from southwestern Laurentia (Mulder et al., 2017) and Kentucky (Moecher, Bowersox, & Hickman, 2018), and perhaps the Middle Run. In contrast, there is a large Ottawa peak and a smaller Shawinigan peak for rocks in the Amundsen and Mackenzie basins of northwest Canada.…”
Section: Discussionmentioning
confidence: 99%